Предмет: Алгебра, автор: rasul97

√ 3x+1-√x-1=2

 

 

√ x+3 + √ 3x-2=7

  

 

 1+x  В первом√   √  x² +24=x+1

 

 

 

 

14(1+√31)+(7-√31)²

(√2-√15)²+(√6+√5)²

 

√    464   

  39²-10²

 

128²-41²

   156²-69²

Ответы

Автор ответа: Fedor
0

sqrt(3x+1)-sqrt(x-1)=2

(sqrt(3x+1)-sqrt(x-1))^2=2^2

(3x+1)-2sqrt(3x+1)(x-1)+(x-1))=4

4x-4=2sqrt(3x+1)(x-1)

2x-2=sqrt(3x^2-3x+x-1)

(2x-2)^2=(sqrt(3x^2-3x+x-1))^2

4x^2-8x+4=3x^2-3x+x-1

x^2-6x+5=0

D=b^2-4ac=36-20=16

x1,2=(-b±sqrt(D))/2a

x1,2=(6±4)/2

x1=5

x2=1

 

Похожие вопросы
Предмет: История, автор: nektodisa